UNDERGRADUATE ELT STUDENTS’ SPEAKING ANXIETY IN THE USE OF E-LEARNING IN INDONESIA - Wahyuddin Wahyuddin; Chairil Anwar Korompot; Sultan Baa (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
The pandemic of COVID-19 has brought a heavy pressure to the world in early 2020. During this pandemic, many schools and universities from the entire world in order to decrease the outbreak of COVID-19, the learning process has moved to an efficient way or alternative methods of learning during this crisis through e-learning. There are many applications of e-learning used for online learning in Indonesian education setting to date, but one of the most frequently used by the teachers is Zoom application. Speaking in English via Zoom, students certainly experience various obstacles. Each student has different psychological condition, where some students can speak English via Zoom confidently and some students also cannot speak English via Zoom because they are shy or nervous. This study aimed to discover the level of students’ speaking anxiety and identify factors to contribute the speaking anxiety in an EFL classroom via Zoom. This study used a mixed method research design to answer the problem of the study. Twenty seven (27) students of English Education Department of IAIN Kendari and purposive sampling was used in which the respondents that were being selected for the interview were seven students who study using e-learning, especially Zoom and students that have higher level of speaking anxiety. The instruments used for this study were FLCAS (Foreign Language Classroom Anxiety Scale) questionnaire and interview concerning speaking anxiety via Zoom. Due to the pandemic that is currently happening, the questionnaire was administrated online and interview was done through voice call and had been recorded under permission. From 33 items of FLCAS questionnaire answered by 27 students to find the speaking anxiety level, this study found that there were 4 students (14.81%) who were in “Very Anxious” level, 8 students (29.63%) were in “Anxious” level and most students in which 11 students (40.74%) experienced “Mildly Anxious” level of speaking anxiety in the use Zoom. After finding out seven students who have highest level of speaking anxiety, interview was conducted with six items to find out factors contribute speaking anxiety and there were four factors which were found in the study, they are; speaking in front of the class, being laughed at by friends, teacher’s personality and attitude and students’ beliefs about English